Peningkatan Pembelajaran Gaya Bahasa dengan Metode Inquiri pada Peserta Didik Kelas X SMA Ar-Rosyidah Magetan Semester 2 Tahun Pelajaran 2021/2022 - Rifa'i, Syawaludin Nur (UPA Bahasa Universitas Tidar And HISKI Kedu, 2022)
This study aims to describe the Inquiry approach as an effort to improve language style learning in class X high school students Ar-Rosyidah Magetan. This research was conducted in semester 2 of the 2021/2022 academic year with two cycles, namely cycle 1 and cycle 2. The research subjects were grade X students of Ar-Rosyidah Magetan High School in 2021/2022 as many as 35 students consisting of 11 male students and 24 female students. The study was conducted in 2 cycles, each cycle consisting of four stages, namely action planning, action implementation, observation, and reflection. Data collection using the method of observation and student performance test methods. The results of the study concluded that the application of the inquiry method could improve the learning of the language style of X grade students of Ar-Rosyidah Magetan High School. This can be proven by the results of students' learning completeness. The results of mastery learning in cycle 1 = 57% and cycle 2 = 85%.